A companion to twelfth-century schools - Giraud, Cédric 1977- (Leiden Boston Brill, 2020)
"The ambition of this Companion to Twelfth-Century Schools is to provide an update on the research regarding a question that has seen many renewals in the last three decades. The discovery of new texts, the progress made in critical attribution, the growing attention given to the conditions surrounding the oral and written dissemination of works, the use of the notion of "community of learning", the reinterpretation of the relations between the cloister and the urban school, the link between institutional history and social history, in short, the entire contemporary renewal of cultural history within international medieval studies allow to offer a new synthesis on the schools of the 12th century. Contributors are: Alexander Andrée, Irene Caiazzo, Cédric Giraud, Frédéric Goubier, Danielle Jacquart, Thierry Kouamé, Constant J. Mews, Ken Pennington, Dominique Poirel, Irène Rosier-Catach, Sita Steckel, Jacques Verger, and Olga Weijers"--
Includes bibliographic reference and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Education, Medieval; Intellectual life -- History -- To 1500; Civilization, Medieval -- 12th century; Europe -- Intellectual life; Aufsatzsammlung